Interaksi Antara Protein Morfogenetik Tulang, Kalsifikasi Vaskular, dan Sindrom Metabolik: Mekanisme dan Perspektif Terapi - Fransiska Sihotang; Budi Satrijo (Jurnal Klinik dan Riset Kesehatan, 2026)
Vascular calcification (VC) is a pathological process marked by the abnormal deposition of calcium phosphate in the vascular wall, leading to increased arterial stiffness and the development of cardiovascular disease. Previously considered as a passive degenerative condition, vascular calcification is now understood as an actively regulated process involving vascular smooth muscle cells (VSMCs) and is influenced by metabolic disorders, especially metabolic syndrome (MetS). Metabolic syndrome, defined by insulin resistance, hypertension, dyslipidaemia, and central obesity, promotes vascular calcification via various molecular mechanisms, such as chronic inflammation, oxidative stress, and lipid dysregulation. Bone morphogenetic proteins (BMPs), particularly BMP-2, are essential for the osteogenic differentiation of vascular smooth muscle cells, facilitating vascular mineralisation and influencing cardiovascular morbidity. Increased BMP signalling in metabolic syndrome is associated with heightened vascular stiffness, endothelial dysfunction, and greater arterial calcification. This review examines the intricate relationship between vascular complications and metabolic syndrome, highlighting the role of bone morphogenetic proteins in vascular pathology. An enhanced comprehension of these molecular mechanisms may facilitate the development of novel treatment strategies designed to mitigate cardiovascular risk and enhance patient outcomes.